Tanggung Jawab Perusahaan Terhadap Proses Jual Beli Non-Prosedural oleh Karyawan (Salinan Putusan Nomor 1666 K/PDT/2022) - Kumalasari, Ganit Fitria; Angelina, Sandra Laudya; Zevanya, Keisha; Putri, Naurah Arista; Setyo, Pradana Adji; Ramadhani, Dwi Aryanti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines corporate civil liability for employees’ non-procedural gold trading activities based on the Supreme Court Decision No. 1666 K/Pdt/2022. The analysis focuses on the application of Articles 1365 and 1367 of the Indonesian Civil Code to determine the extent of a company’s responsibility when an employee commits an unlawful act within the scope of employment. Employing a normative juridical approach through statutory analysis, doctrinal review, and judicial reasoning assessment, this research reveals that the Supreme Court upheld joint and several liability between PT AT Tbk. and its employees for losses arising from an improper gold transaction, affirming that the corporation remains liable for wrongful acts committed by its staff during the execution of their official duties. The ruling strengthens the legal concept of vicarious liability in modern corporate practice and constitutes an important precedent for consumer protection and legal certainty in high-value commercial transactions.